Hospital-acquired Acute Kidney Injury: An Analysis of Nadir-to-Peak Serum Creatinine Increments Stratified by Baseline Estimated GFR - Broce, Jose Calvo (American Society of Nephrology, 2011)
SUMMARY: BACKGROUND AND OBJECTIVES: Serum creatinine (sCr) increments currently used to define acute kidney injury (AKI) do not take into consideration the baseline level of kidney function. The objective of this study was to establish whether baseline estimated GFR (eGFR) provides additional risk stratification to sCr-based increments for defining AKI. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: 29,645 adults hospitalized at an acute care facility were analyzed. Hospital-acquired AKI was defined by calculating the difference between the nadir and subsequent peak sCr. RESULTS: Different thresholds of nadir-to-peak sCr were found to be independently associated with increased in-hospital mortality according to baseline eGFR strata. A nadir-to-peak sCr minimum threshold of ≥0.2, ≥0.3, and ≥0.5 mg/dl was required to be independently associated with increased in-hospital mortality among patients with baseline eGFR ≥60 ml/min per 1.73 m(2) (odds ratio [OR] 1.67; 95% confidence interval [CI] 1.13 to 2.47), 30 to 59 ml/min per 1.73 m(2) (OR 2.69; 95% CI, 1.82 to 3.97), and <30 ml/min per 1.73 m(2) (OR 2.15; 95% CI 1.02 to 4.51), respectively. There was a significant interaction between the nadir-to-peak sCr and baseline eGFR for in-hospital mortality (P < 0.001). Using these thresholds, survivors of AKI episodes had an increased hospital length of stay and were more likely to be discharged to a facility rather than home. Sensitivity analyses showed a significant interaction between baseline eGFR strata and relative increases in sCr, as well as absolute and relative decreases in eGFR for in-hospital mortality (P < 0.001). CONCLUSIONS: This study suggests that future sCr-based definitions of AKI should take into consideration baseline eGFR.